The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0013161x19851174
|View full text |Cite
|
Sign up to set email alerts
|

Tight, Loose, or Decoupling? A National Study of the Decision-Making Power Relationship Between District Central Offices and School Principals

Abstract: Do school district central offices and school principals have the same level of influence on school decisions? What does the district–principal power relationship look like? These two questions are discussed but are rarely examined in the literature. Based on a nationally representative sample from the 2007-2008 Schools and Staffing Survey data, we explored these two questions. Specifically, we applied the paired samples t test to compare the district central offices’ and school principals’ influences and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…As mentioned in the foregoing, Shen and Ma (2006), studying the relationship among the state's curriculum guidelines, schools' curriculum and classroom teachers' instruction, found that state's curriculum guidelines and schools' curriculum were tightly aligned and that the influence of states and schools stopped at the classroom door. Most recently, they found that the relationship between the school and the classroom was loose (Shen et al, 2017), but the relationship between the district and the school was very tight, particularly in the technical core of schooling (performance standards, establishing curriculum, and teachers' professional development programs) (Xia et al, 2020). The summary of the above empirical findings, all based on multi-level analyses of nationally representative data, suggests that the educational system is not loosely coupled throughout, as previously thought.…”
Section: A Bifurcated Educational Systemmentioning
confidence: 74%
“…As mentioned in the foregoing, Shen and Ma (2006), studying the relationship among the state's curriculum guidelines, schools' curriculum and classroom teachers' instruction, found that state's curriculum guidelines and schools' curriculum were tightly aligned and that the influence of states and schools stopped at the classroom door. Most recently, they found that the relationship between the school and the classroom was loose (Shen et al, 2017), but the relationship between the district and the school was very tight, particularly in the technical core of schooling (performance standards, establishing curriculum, and teachers' professional development programs) (Xia et al, 2020). The summary of the above empirical findings, all based on multi-level analyses of nationally representative data, suggests that the educational system is not loosely coupled throughout, as previously thought.…”
Section: A Bifurcated Educational Systemmentioning
confidence: 74%
“…According to Xia et al (2019) investigated the nature of decision making was shown to be tightly coupled in areas such as performance standards, curriculum, and professional development, a loose coupling was identified in the area of budget and financial oversight. In addition to that, identified that while budget remains a central facet of the school operational decisionmaking process, loose coupling has allowed much of the financial decision making to be shifted to the principal level in the sample population.…”
Section: Level Of Shared Responsibilitymentioning
confidence: 99%
“…More recent works empirically investigate the symbiotic relationship in school strategy between school district administration and local schools. Xia et al (2020) found that dimensions of professional commitment strategy appeared in areas of professional development of teachers, self-evaluation of teacher practices, and discipline policies. On the other hand, external control appeared in the areas of defining performance standards, establishing local curriculum, and defining standards for professional development.…”
Section: External Control Versus Professional Commitmentmentioning
confidence: 99%